Disrupted Lipid Raft Shuttling of FcεRI by n-3 Polyunsaturated Fatty Acid Is Associated With Ligation of G Protein-Coupled Receptor 120 (GPR120) in Human Mast Cell Line LAD2 - Wang, Xiaofeng; Ilarraza, Ramses; Tancowny, Brian P.; Alam, Syed Benazir; Kulka, Marianna (Frontiers in Nutrition, 2020)
n-3 polyunsaturated fatty acids (PUFA) have been reported to promote health in a variety of disease conditions, such as hypertension, heart disease, diabetes, cancer and allergic diseases, by modulating membrane constitution, inhibiting production of proinflammatory eicosanoids and cytokines, and binding to cell surface and nuclear receptors. We have previously shown that n-3 PUFA inhibit mast cells activation through disrupting FcRI lipid raft partitioning and subsequent suppression of high affinity IgE receptor (FcεRI) signalling in mouse bone marrow-derived mast cells. However, it is still largely unknown how n-3 PUFA modulate human mast cell function, which could be attributed to multiple mechanisms. In the present study, in LAD2 human mast cells, we confirmed similar modulating effect of n-3 PUFA on FcRI lipid raft shuttling, FcRI signaling, and mediator release after cell activation through FcRI. We further showed that these effects are at least partially associated with ligation of G protein-coupled receptor 120 expressed on LAD2 cells, which advanced our mechanistic knowledge of n-3 PUFA’s effect on mast cells and opened novel research direction of interplay between n-3 PUFA, lipid rafts, FcRI, and G protein-coupled receptor 120. Future research in this direction may present new targets for nutritional intervention and therapeutic agents.